Use of health communication materials by health-care providers for health education in low- and middle-income countries: A scoping review - Amlaku Nigusie Yirsaw; Gebeyehu Lakew; Adane Nigusie (PLoS ONE, 2026)
Background Health communication materials (HCMs) are widely used to support health education and promotion activities in clinical and community settings. However, evidence regarding their use by healthcare providers in low- and middle-income countries (LMICs) remains inconsistent. This scoping review aims to systematically map and describe the existing literature on the utilization of health communication materials by healthcare providers in low- and middle-income countries (LMICs). Methods This scoping review was conducted in accordance with the PRISMA-ScR reporting guideline and the Joanna Briggs Institute (JBI) framework for scoping reviews. The studies were searched from database inception to September 2025 using electronic databases (PubMed, ScienceDirect, Cochrane, and Hinari) were searched, and studies were selected based on predefined inclusion and exclusion criteria aligned with the Population–Concept–Context framework. Data extraction was performed using a standardized form, and findings were narratively synthesized spreadsheet by two independent reviewers. Findings were synthesized using descriptive numerical analysis and thematic analysis. Result A total of 728 records were identified. 715 were screened after removing duplicates. Following title/abstract and full-text review, 18 studies were included. HCMs, including printed, audiovisual, and electronic tools, were covered in these studies. NGO support, perceived utility, and material accessibility were facilitators, while organizational limitations, patient disengagement, limited availability, and inadequate training were major obstacles. Conclusion The use of health communication materials by healthcare providers in LMICs is influenced by contextual, institutional, and individual factors. While HCMs are widely available in many settings, their use remains inconsistent and is influenced by systemic challenges. Strengthening accessibility, provider training, culturally appropriate content, and integration into routine care may support improved implementation.